Governance of health emergencies - Stocking, Barbara; Gostin, Lawrence; Halton, Jane; Saavedra, Jorge; Garcia, Patricia; Leite, Ricardo Baptiste; Jemilah, Mahmood *; Mpanju, Winnie; Gurria, Angel; Elil, Renganathan * (Elsevier, 2023)
There have been many analyses of the COVID-19 pandemic but little discussion of the governance failures, especially the need for cross-government, multisectoral engagement, and leadership by heads of state and governments at both national and global levels.